2021
DOI: 10.2174/1573406416666200403075826
|View full text |Cite
|
Sign up to set email alerts
|

2,4-Thiazolidinedione as Precursor to the Synthesis of Compounds with Anti-glioma Activities in C6 and GL261 Cells

Abstract: Objective: This study aims to synthesize and characterize 2,4-thiazolidinediones and evaluate their antitumor activity. Method: TZDs were synthesized from three components: 2,4-thiazolidinedione, arene-aldehydes, and aryl chlorides. The reactions were carried out inside a microwave and monitored using thin-layer chromatography (TLC). Compounds were identified and characterized using gas chromatography coupled to mass spectrometry (CG-MS) and hydrogen (1 H-NMR) and carbon nuclear magnetic resonance spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…There have been several studies determining the anticancer effects of 4-thiazolidinone derivatives. More commonly studied derivatives are thiazolidine and 4-thiazolidinone, and it has been shown that these molecules have anticancer effects on several cancers including chronic myeloid leukemia, lung carcinoma, breast cancer, prostate cancer, oral cancer, colorectal cancer, neuroblastoma, and glioma [ 27 32 ]. While thiazolidine and 4-thiazolidinone derivatives exhibit different mechanisms of action to exert their anticancer effects, only a few of many studies reported their relation with autophagy pathways [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies determining the anticancer effects of 4-thiazolidinone derivatives. More commonly studied derivatives are thiazolidine and 4-thiazolidinone, and it has been shown that these molecules have anticancer effects on several cancers including chronic myeloid leukemia, lung carcinoma, breast cancer, prostate cancer, oral cancer, colorectal cancer, neuroblastoma, and glioma [ 27 32 ]. While thiazolidine and 4-thiazolidinone derivatives exhibit different mechanisms of action to exert their anticancer effects, only a few of many studies reported their relation with autophagy pathways [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…This discussion will encompass the nuances of structure-activity relationships, providing a rational framework for interpreting observed biological activities. [19,20] This review seeks to provide a holistic view of the use of imidazolidinone derivatives as pioneering anticancer agents. By unraveling insights from their synthesis to structure-activity exploration, we aim to contribute valuable knowledge to the field of medicinal chemistry, guiding future research endeavors toward the development of innovative and effective anticancer therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…As we explore the in vitro anticancer activities of imidazolidinone derivatives, a comprehensive understanding of their efficacy in different cancer cell lines and animal models will be presented. This discussion will encompass the nuances of structure‐activity relationships, providing a rational framework for interpreting observed biological activities [19,20] . This review seeks to provide a holistic view of the use of imidazolidinone derivatives as pioneering anticancer agents.…”
Section: Introductionmentioning
confidence: 99%